2019
DOI: 10.3389/fneur.2019.00407
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Remifentanil Against Excitotoxic Brain Damage in Newborn Mice

Abstract: Background: Remifentanil, a synthetic opioid used for analgesia during cesarean sections, has been shown in ex vivo experiments to exert anti-apoptotic activity on immature mice brains. The present study aimed to characterize the impact of remifentanil on brain lesions using an in vivo model of excitotoxic neonatal brain injury. Methods: Postnatal day 2 (P2) mice received three intraperitoneal injections of remifentanil (500 ng/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…with remifentanil (30 μg/kg in total; 091110, Yichang Renfu Pharmaceutical Industry) 3 times, and were then injected (i.p.) twice with 1 μL of lentivirus at a concentration of 5 × 10 8 TU/mL each time 33‐35 . Animal use and experimental procedures were carried out in a protocol approved by the Experimental Animal Ethics Committee of Xi'an Jiaotong University.…”
Section: Methodsmentioning
confidence: 99%
“…with remifentanil (30 μg/kg in total; 091110, Yichang Renfu Pharmaceutical Industry) 3 times, and were then injected (i.p.) twice with 1 μL of lentivirus at a concentration of 5 × 10 8 TU/mL each time 33‐35 . Animal use and experimental procedures were carried out in a protocol approved by the Experimental Animal Ethics Committee of Xi'an Jiaotong University.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with remifentanil influences neutrophil migration through endothelial cell monolayers, as well as adhesion molecule expression [14]. Moreover, remifentanil is proved to exert protective effect in a variety of diseases, such as acute lung injury, ischemia/reperfusion injury, and excitotoxic brain damage [5,15,16]. However, the potential role and mechanism of remifentanil in sepsis has not been yet fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed to establish safety profiles for the use of ketamine in neonates due to concerns regarding possible neurotoxicity in animal studies (22). Regarding remifentanil, studies performed in mice have shown that it has an antiapoptotic impact and that it exerts beneficial effects against excitotoxicity on the developing mouse brain that is associated with a reduction in the brain lesion size as well as prevention of a number of behavioral deficits in young mice (23, 24). It should be noted that the neurotoxicity of some anesthetic agents has mainly been demonstrated in animals, and most of the time in the absence of painful procedures.…”
Section: Discussionmentioning
confidence: 99%